Tales from venus - "Chandra, Neelam Saxena" (New Delhi, 2018)
There are tales that tickle your bones, tales that make you feel emotional, tales of courage, tales of treachery, tales that thrill you and tales that make you happy. Ultimately, you are bound to remain glued to the book because of the surprise element offered by each story.
Keywords: Women - India - Fiction; IRSEE as an author